2010
DOI: 10.1007/s00467-010-1729-1
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine after pediatric kidney transplant: a Midwest Pediatric Nephrology Consortium study

Abstract: The main aim of this study was to compare the response to trivalent inactivated influenza vaccine in children who received a kidney transplant and were on steroid-free versus steroid-based immunosuppression. Groups: 1. Kidney transplant recipients on steroid-free immunosuppression (n=27); 2. Kidney transplant recipients on steroid-based immunosuppression (n=39); 3. Healthy controls (n=21). Hemagglutination inhibition titers against 2007-2008 A/H1N1 and A/H3N2 and B strains were measured before and 8 weeks post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…In total, 36 trials on inactivated trivalent influenza vaccination after SOT were included in the review with publication dates ranging from 1980 to 2011 and vaccines against the circulating strains of the influenza season of 1981/82 to 2007/2008 [13][15], [32][64].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 36 trials on inactivated trivalent influenza vaccination after SOT were included in the review with publication dates ranging from 1980 to 2011 and vaccines against the circulating strains of the influenza season of 1981/82 to 2007/2008 [13][15], [32][64].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, recent reports in pediatric kidney transplant recipients show variable seroprotective responses ranging from 31% to 85% depending on the vaccine strain (65,66). In a cohort of children postliver transplant, Mack et al reported that younger age and shorter posttransplant time were factors for poorer vaccine response.…”
Section: Pediatric Issuesmentioning
confidence: 99%
“…In one study, kidney transplant recipients who were 3-10 years posttransplant had a 93% seroprotection rate to A(H1N1) antigen after vaccination (232). Among persons with kidney or heart transplants, seroresponse rates were similar or slightly reduced compared with healthy persons (232)(233)(234)(235)(236)(237). However, a small study involving participants with liver transplants indicated a reduced immunologic response to influenza vaccinations (238).…”
Section: Immunocompromised Personsmentioning
confidence: 99%